2015
DOI: 10.1186/s40780-014-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-managed clinics for patient education and counseling in Japan: current status and future perspectives

Abstract: To improve the adherence to and knowledge about pharmacotherapy in outpatients and to maximize the efficacy and minimize the adverse drug events, the first pharmacist-managed clinic (PMC) in Japan was established for anticoagulation therapy at Nagoya University Hospital in 2000. Since then, various PMCs such as for asthma/chronic obstructive pulmonary disease, Alzheimer’s disease, hypercholesterolemia, chronic hepatitis C, cancer chemotherapy, palliative care, chronic kidney disease, and continuous ambulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 76 publications
0
22
0
3
Order By: Relevance
“…Pharmacist counseling has been shown to improve patients’ and caregivers’ knowledge in various chronic conditions . Increase in knowledge can potentially improve treatment compliance, leading to disease improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacist counseling has been shown to improve patients’ and caregivers’ knowledge in various chronic conditions . Increase in knowledge can potentially improve treatment compliance, leading to disease improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist counseling has been shown to improve patients' and caregivers' knowledge in various chronic conditions. [10][11][12] Increase in knowledge can potentially improve treatment compliance, leading to disease improvement. We postulate that a pharmacist-led counseling service for caregivers of pediatric AD patients may lead to similar improvements in disease control.…”
mentioning
confidence: 99%
“…So, many reports have proved that pharmacist oriented counseling services played the key roles on such regions as chronic conditions self-medication managements, [13,14] adverse drug event reduction, [15] over-the-counter therapy management, [16] and so on. Otherwise, Wibowo et al [17] also found some barriers that influenced the pharmacist services.…”
Section: Introductionmentioning
confidence: 99%
“…9) In this study, we compared patients undergoing chemotherapy for cancer who were managed by physicians alone with those managed in collaboration with oncology pharmacists. Specifically, we investigated the effects of such collaboration on therapeutic outcomes and medical costs.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, no study has yet addressed the effect of collaboration between oncology pharmacists and physicians on therapeutic outcomes and medical costs in Japan. 9) In this study, we compared patients undergoing chemotherapy for cancer who were managed by physicians alone with those managed in collaboration with oncology pharmacists. Specifically, we investigated the effects of such collaboration on therapeutic outcomes and medical costs.…”
mentioning
confidence: 99%